2018
DOI: 10.3389/fmicb.2018.01408
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phylogenetic Characteristics of Pasteurella multocida Isolates From Different Host Species

Abstract: Pasteurella multocida is a leading cause of respiratory diseases in many host species. To understand the genetic characteristics of P. multocida strains isolated from different host species, we sequenced the genomic DNA of P. multocida isolated from pigs and analyzed the genetic characteristics of strains from avian species, bovine species, pigs, and rabbits using whole genome sequence (WGS) data. Our results found that a capsular: lipopolysaccharide (LPS): multilocus sequence typing (MLST) genotype A: L1: ST1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 53 publications
3
59
0
Order By: Relevance
“…These 2 strains, were genetically analysed using partial 16S rRNA and rpoB gene sequence comparison, the most used genes for Pasteurella species identification and phylogeny [28]. Phylogenetic study revealed that both P. multocida A ovine isolates (S14 and S13) are related to strains from different host species (bovine, porcine and avian), suggesting that this type is not specific to one animal species and may cause haemorrhagic septicaemia in pigs, cattle and avian hosts; which is in accordance with other previous phylogenetic studies [29][30][31]. Thus, the transmission of bacteria between different host species, may constitute a factor in the population biology of P. multocida [32].…”
Section: Discussionsupporting
confidence: 86%
“…These 2 strains, were genetically analysed using partial 16S rRNA and rpoB gene sequence comparison, the most used genes for Pasteurella species identification and phylogeny [28]. Phylogenetic study revealed that both P. multocida A ovine isolates (S14 and S13) are related to strains from different host species (bovine, porcine and avian), suggesting that this type is not specific to one animal species and may cause haemorrhagic septicaemia in pigs, cattle and avian hosts; which is in accordance with other previous phylogenetic studies [29][30][31]. Thus, the transmission of bacteria between different host species, may constitute a factor in the population biology of P. multocida [32].…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies shown primers speci c for P. multocida (KMT1) and its ve capsular genotypes (A, B, D, E, F) [14], eight LPS genotypes (L1 ~ L8) [15], as well as 23 kinds of virulence factors-encoding genes (VFGs) commonly detected in epidemiological studies (ptfA, mA, hsf-1, hsf-2, pfhA, tadD, toxA, exbB, exbD, tonB, hgbA, hgbB, fur, tbpA, nanB, nanH, pmHAS, ompA, ompH, oma87, plpB, sodA and sodC) [5]. Therefore, we extracted those primers-targeted nucleotide sequences (Supplementary Txt 1) from the complete genome sequences of our previously sequenced P. multocida strains, including HB01 (serogroup A) [24], HN04 (serogroup B) [23], HN06 (serogroup D, producing toxin) [25], and HN07 (serogroup F) [26]. These nucleotide sequences were then stored on a CentOS server.…”
Section: Development and Implementation Of Pmgtmentioning
confidence: 99%
“…In 2017, a virulence genotyping system based on the detection of different virulence factor gene (VFG) pro les was also reported for distinguishing P. multocida strains from different hosts [18]. Compared to the traditional serological typing methods, these molecular DNA-based typing systems are indeed highly effective and accurate, and they are now wildly used to determine the epidemiological and genetic characteristics of clinical isolates [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(accession number CP003022), HB01 (accession number CP006976), HB03 (accession number CP003328), FDAARGOS_218 (accession number CP020405), PM70 (accession number AE004439), CIRMBP-0884 (accession number CP020345), PMTB2.1 (accession number CP007205), HN06 (accession number CP003313), and HN07 (accession number CP007040), were downloaded from the NCBI genome database. Nine HA biosynthetic genes (glck, pgi, pgm, galU, hyaC, glmS, glmM, glmU, and hyaD) previously described from the study of Mao et al (2009) [1] were used to search for orthologous nucleotide sequences in the obtained P. multocida genomes using BLASTn [47]. A similar search was performed against the genomes of Homo sapiens, E. coli strain K-12 MG1655, Streptococcus pyogenes strain M1, and S. thermophilus to identify orthologous genes according to previous reports [48,49], which studied the HA production of these strains, except E. coli, which is often used for the expression of recombinant HA biosynthesis enzymes.…”
Section: Identi Cation Of Hyaluronic Acid Biosynthetic Genesmentioning
confidence: 99%